Reação de genótipos de Coffea canephora à Hemileia vastatrix - Mendonça, Rodolfo Ferreira de (2013)
The Espírito Santo state is the larger producer of conilon coffee in Brazil, and the leaf rust disease is considered the main disease of this culture. Genotypes of conilon coffee may have different behavior in relation to leaf rust. Within this approach,